The Adaptation of Building Information Modelling (BIM) on Existing As-Built Plan for Future Engineering Reference: Case Study: Bangunan Tempat Letak Kereta, Pusat Perubatan Universiti Kebangsaan Malaysia (PPUKM) - Kasim, Nurul Nasuha; Dr. Muhammad Nizam bin Zakaria, (Recent Trends in Civil Engineering and Built Environment, 2023)
Building Information Modeling (BIM) is a new alternative approach from construction schemes that replaces conventional methods. BIM is also a collaborative tool used by the architecture, engineering and construction (AEC) industry based on various software solutions. Currently, most of the BIM processes are being developed for new structures. Therefore, it is difficult for engineers to refer to most existing buildings in the future. The purpose of this study is to facilitate engineers in obtaining all data for maintenances and operation buildings in the future. Therefore, the analysis and design of the existing building in “Bangunan Tempat Letak Kereta di Pusat Perubatan Universiti Kebangsaan Malaysia (PPUKM)” was conducted to obtain detailed data on the materials used in the building such as the type of building materials, size of reinforcement and others related things. In addition, this study was also conducted to compare the design results of the building using conventional design software with an existing As-built plan. Literature review is also useful to get information on the use of BIM in existing buildings and its benefits. This study was also conducted with the tools of BIM software which are Tekla Structural Designer  for analyse and design the building structure and Autodesk Revit Structure for modelling the building. Therefore, the software will help to documentation in detail the design of steel and concrete in 3 dimensional concepts. Thus, the model elements are directly presentation of information from the building database for engineering reference in future. Keywords: Building Information Modelling, engineering reference, existing building, Autodesk Revit.